Trace formulae for graph Laplacians with applications to recovering matching conditions - Kiselev, A. V.; Ershova, Yu. (Methods of Functional Analysis and Topology, 2012)
Graph Laplacians on finite compact metric graphs are considered under the assumption that the matching conditions at the graph vertices are of either δ or δ’ type. In either case, an infinite series of trace formulae which link together two different graph Laplacians provided that their spectra coincide is derived. Applications are given to the problem of reconstructing matching conditions for a graph Laplacian based on its spectrum.